2007
DOI: 10.1007/s11165-006-9032-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Learning in an Out-of-school Context: The Cognitive and Affective Impact of Two Cryogenics-based Enrichment Programmes on Upper Primary Students

Abstract: Concepts learned in the classroom were reinforced and augmented by presenting them in a different context using cryogenics-based enrichment programmes (CBEPs) held in an out-of-school setting. The effectiveness of two CBEPs, which involve the use of liquid nitrogen and liquid oxygen, was explored. Using a sample of 265 upper primary students, it was found that both enrichment programmes were effective in promoting the learning of science concepts. Fair improvements, albeit only transient, in two attitude const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Attitude toward science is also positively related to the selection of science courses (Miller, Lietz, & Kotte, 2002; Simpson & Oliver, 1990). Several studies have shown that attitudes toward science can be improved by means of a science-based program (Caleon & Subramaniam, 2007; Moore, 2001). However, most studies on attitudes toward science involved mainstream children, and studies dealing with the attitudes of intellectually gifted children remain scarce (Caleon & Subramaniam, 2008).…”
Section: Enrichment Program Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude toward science is also positively related to the selection of science courses (Miller, Lietz, & Kotte, 2002; Simpson & Oliver, 1990). Several studies have shown that attitudes toward science can be improved by means of a science-based program (Caleon & Subramaniam, 2007; Moore, 2001). However, most studies on attitudes toward science involved mainstream children, and studies dealing with the attitudes of intellectually gifted children remain scarce (Caleon & Subramaniam, 2008).…”
Section: Enrichment Program Effectsmentioning
confidence: 99%
“…Finally, it was expected that due to the special focus of the enrichment program on science and technology, the attitudes of the participating gifted children toward science would improve (cf. Caleon & Subramaniam, 2007; Moore, 2001).…”
Section: The Present Studymentioning
confidence: 99%
“…This is an important aspect of scientific understanding (see Brophy, 1999, for an extended discussion of the role of motivation for learning, and Anderman & Young, 1994, for its relevance to learning science in particular). If students do not value or feel they can be successful in understanding school science, they develop a negative attitude toward science learning, and this can have an impact on their achievement and choice of career (Caleon & Subramaniam, 2007; Nair, 2003; Osborne, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Applying the scheme in Table to the studies included in the Taylor et al () meta‐analysis, we found that 7/97 studies (7.2%) could be considered either a direct or a conceptual replication with two direct replications (Davis, ; Lertwanasiriwan, ) and five conceptual replications (Anderson, ; Caleon & Subramaniam, ; Chang, Quintana, & Krajcik, ; Pyke, Lynch, Kuipers, Szesze, & Watson, , ). Five of the seven replications were unpublished manuscripts or doctoral dissertations.…”
Section: Emergent Themes From Synthesis Projectsmentioning
confidence: 99%